Innovative perception analysis of HIV prevention messaging for black women in college: a proof of concept study - Rasheeta Chandler; Henry Ross; Dominique Guillaume (BMC, 2022)
Abstract Background Black women in college are disproportionately affected by HIV, but have not been a population of focus for HIV prevention campaigns. This study used content from a preexisting HIV media campaign to assess its relevancy and acceptability among Black women in college. Methods Media viewing and listening sessions were convened with Black women enrolled at an HBCU (n = 10) using perception analyzer technology-hardware and software tools that are calibrated to gather and interpret continuous, in-the-moment feedback. Matched pre-and-post-test responses from focus groups were obtained from the perception analyzer data. Descriptive statistics and t-tests were used to characterize the data. Results Students were more likely to personally identify with media content that included profound statements, along with memorable people and actors [95% CI: 1.38, 2.27]. In over half of the vignettes, participants reported that content representing students' society, culture, or interests was missing. Conclusions HIV prevention media campaigns may offer potential in increasing HIV awareness and risk perceptions; further research is needed to evaluate optimal content tailoring for both cultural and climate relevancy.